2016
DOI: 10.1021/acssuschemeng.6b00226
|View full text |Cite
|
Sign up to set email alerts
|

Products and Kinetics for Isothermal Hydrothermal Liquefaction of Soy Protein Concentrate

Abstract: Soy protein concentrate was hydrothermally treated at isothermal temperatures of 200, 250, 300, and 350 °C for times up to 60 min to produce a crude bio-oil. Additional product fractions included water-soluble products, gases, and residual solids. We report herein the conversion of protein and gravimetric yields of the different product fractions. The biocrude yield generally increased with both time and temperature as did the yield of gaseous products. The highest biocrude yield was 34%, produced from liquefa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 20 publications
6
49
0
Order By: Relevance
“…Mathematica 10.2 was employed to solve the system of ordinary differential equations and simultaneously estimate the A i (Arrhenius pre-exponential factors) and E i (activation energies) of hydrothermal HCO 3 – reduction by minimizing the sum of squared residuals (SSR) as eq 1 . 30 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Mathematica 10.2 was employed to solve the system of ordinary differential equations and simultaneously estimate the A i (Arrhenius pre-exponential factors) and E i (activation energies) of hydrothermal HCO 3 – reduction by minimizing the sum of squared residuals (SSR) as eq 1 . 30 …”
Section: Results and Discussionmentioning
confidence: 99%
“…The energy recoveries in this study for casein are consistent with prior reports on isothermal HTL of crude algal protein, soya protein, egg albumin, and bovine serum albumin (calculated based on reported elemental compositions) where energy recoveries were 11.7%–30.5%. Luo et al and Teri et al, on the other hand, produced biocrude with 60.6% and 54.7% (calculated based on reported elemental compositions) energy recovery from soy protein concentrate and soy protein, respectively, under similar isothermal reaction conditions, and Sheehan et al achieved high energy recoveries of 65% after fast HTL of soy protein isolate . The higher energy recoveries from soy protein concentrate and soy protein isolate are a direct result of the higher biocrude yields reported for these proteins.…”
Section: Resultsmentioning
confidence: 99%
“…These values for the nitrogen recovery in the aqueous phase are within the range of those reported previously. Luo et al observed ∼50% N recovery from isothermal HTL of soy protein concentrate at 200–350 °C for 10 min . Valdez et al reported ∼75% N distribution in the aqueous phase from isothermal HTL of microalgae over a range of reaction conditions (250–400 °C, 10–90 min) .…”
Section: Resultsmentioning
confidence: 99%
“…These values are similar to the biocrude yields reported from HTL of castor oil (∼85%), sunflower oil (∼85%), casein (∼20%), and soy protein (∼25%) at similar conditions. 3,5,20 The biocrude yields from HTL of the lignocellulose model compounds are much lower. They are 4.6, 6.6, and 1.4 wt % for cellulose, xylose, and lignin, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%